DINAMIKA KONFLIK DAN IMPLIKASINYA TERHADAP KEAMANAN GLOBAL DALAM PERSPEKTIF HUKUM HUMANITER - Viliala Romadhon; Libra Dian Prasetyawan Yonatan, Tarsisius Susilo, Bungkus Hadisuseno, Bambang Budi Kuncoro (INTELIGENSIA MEDIA, 2025)
The contemporary dynamics of armed conflict exert profound ramifications on global security, particularly through their catalytic role in fostering terrorism and mass migration. What were once localized hostilities have, in the era of globalization and interconnectedness, evolved into transnational threats with far-reaching consequences. This study explores the far-reaching implications of violations of International Humanitarian Law (IHL), which are rampant in modern conflicts—ranging from deliberate attacks on civilians and acts of sexual violence to torture and obstruction of humanitarian assistance. These breaches not only exacerbate humanitarian crises but also dismantle social cohesion, perpetuate impunity and cycles of retaliatory violence, and incite international tensions that undermine peace processes. This analysis elucidates the intrinsic nexus between conflict, IHL, and global security, underscoring how noncompliance with IHL constitutes a pivotal factor in sustaining regional and international instability. The study accentuates the urgent necessity for an integrated approach to safeguarding global security— encompassing preventive diplomacy, the enforcement of legal accountability, humanitarian interventions, security sector reform, and the cultivation of sound governance. It recommends strengthening international cooperation and enhancing awareness and enforcement of IHL as essential measures to effectively address the complex landscape of contemporary conflict and its global security implications